Benchmarking Firm Performance - Dawkins, P.; Feeny, S.; Harris, Mark (Emerald Group Publishing, 2007)
Purpose - The aim of the paper is to provide a framework for benchmarking firm performance (profitability) using panel data. Further, to illustrate how the estimation results can be used for simulation (what if?) exercises.